﻿Role of D2 receptor (-141 C Ins/Del) genetic polymorphism on olanzapine-induced adverse drug reaction in schizophrenic patients - Zahra Jawd Mohammed Ali; Atheer Majid Rashid Al-juhiashi (Pensoft Publishers, 2024)
Olanzapine is commonly prescribed for the management of schizophrenia and is associated with many adverse effects like weight gain, hyperglycemia, and hyperprolactinemia, which may increase the risk of other diseases like diabetes mellitus and cardiovascular diseases. Genetic polymorphism of the D2 receptor may be responsible for the incidence of such adverse effects. This study aimed to assess the role of D2 receptor-141 C Ins/Del (rs1799732) genetic polymorphism and olanzapine-induced adverse effects in Iraqi schizophrenic patients. The case-control study was performed from October 2022 to April 2023 in Al-Hassan Al-Mojtaba Hospital. A total of 100 schizophrenic patients consisting of both genders, aged between 20 and 65 years, were recruited from the Psychiatry Outpatient Department, and 50 apparently healthy without any disease comprising both genders aged 20 to 63 years, served as a control group and were also enrolled in this study. Plasma level of FBS, HbA1c, lipid profile, and prolactin were measured, and genotyping of D2 Receptor-141 C Ins/Del (rs1799732) Polymorphisms was detected using the RFLP method. The heterozygous (Ins/Del) and mutant (Del/Del) alleles of D2 receptor-141 C Ins/Del (rs1799732) was significantly predominated in schizophrenic patient and absent in healthy volunteers. Schizophrenic patients with the deletion allele of D2 receptor-141 C Ins/Del and who were administered olanzapine (rs1799732) exhibited notably higher susceptibility to metabolic adverse effects induced by olanzapine, such as weight gain, hyperglycemia, dyslipidemia, and hyperprolactinemia. In conclusion, the genetic polymorphism of D2 receptor-141 C Ins/Del (rs1799732) was significantly associated with olanzapine induce metabolic adverse effects in Iraqi schizophrenic patients.